An inverse method for structural modification of a subsystem using constrained eigenstructure assignment method to allocate single resonant frequency of whole structure - Kengo MURAKAMI; Yuichi MATSUMURA; Masashi INABA (Nihon Kikai Gakkai ronbunshu, 2025)
NV (Noise and vibration) performance of a mechanical system is determined by the contributions of all subsystems that make up the mechanical system. However, complex mechanical systems such as automobiles are concurrently developed, in which the supplier subsystem is mounted onto the OEM (Original Equipment Manufacturer) subsystem, it is not easy to share intellectual property such as shape information between companies. As a result, NV problems often occur in the final stages of product development. This leads to extensive redevelopment, resulting in longer development times and higher development costs. Therefore, it is necessary to be able to design the NV performance of a whole structure from the supplier's viewpoint at the upstream product development stage. In this paper, we proposed a method to solve the inverse problem of allocating the single resonant frequency of a whole structure, which occurs due to a large contribution from the supplier subsystem, by modifying the structure of the supplier subsystem. This method is composed of kCA (kernel Compliance Analysis) and CEAM (Constrained Eigenstructure Assignment Method), and is realized by using the compliance-FRF matrix of the OEM subsystem provided by the OEM in the upstream design stage. Finally, numerical verification of the proposed method was demonstrated.